GENETIC BREEDING AND ITS RELATED TRAITS ESTIMATION IN JUVENILE AGE IN ERVA-MATE - FERNANDES, José Sebastião Cunha; USHIWATA, Silvio; DAMINELLI, Rebeca de Mattos; GABARDO, Juarez; KOBIYAMA, Massato; MACCARI JUNIOR, Agenor; PREVEDELLO, Celso; RESENDE, Rosângela Maria Simeão; RESENDE, Marcos Deon Vilela; STURION, José Alfredo (Scientia Agraria, 2000)
An 8x8 balanced lattice, with 9 repetitions and 6 plants per plot, performing a total of 3,456 plants (64 half-sib progenies of erva-mate - Ilex paraguariensis St. Hil. - distributed among 5 populations from different sites in the States of Paraná and Rio Grande do Sul), was set up at the Canguiri farm of UFPR. The distances between plants and rows were 1,6 m and 2,5 m respectively. The aim of this trial is to genetically improve these populations as well as to develop other studies considered important for the culture. The traits evaluated were mortality rate at the age of 4 and 12 months, and plant height at 12 months, from the date the trial was set up. The results showed that mortality rate at 4 months was not affected by progenies nor by populations. At twelve months, on the other hand, some progenies and mainly populations showed a higher mortality rate. Significant effects for plant height were detected for populations and progenies within them. Barão de Cotegipe site showed the highest individual narrow sense heritability, the highest average for plant height, and the lowest mortality rate.